2019
DOI: 10.15258/sst.2019.47.3.07
|View full text |Cite
|
Sign up to set email alerts
|

Potential of a single radicle emergence count in predicting field emergence of Desi chickpea seed lots as an alternative vigour test

Abstract: Single early counts of radicle emergence (RE) is a validated vigour test for four crop species. We performed this study to see whether an early radicle emergence (RE) count predicts the emergence of seedlings in Desi chickpea seed lots as well as an electrical conductivity (EC) test. Electrical conductivity measurements of 11 seed lots were highly predictive of field emergence (FE) (R2 = 0.626**). The radicle emergence was counted at regular time intervals of six hours, up to 72 hours after imbibition. Mean ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Seed vigor is an important aspect of seed quality [14]; it is defined as the sum of the properties of the seed that determine the level of activity and the performance of a seed or seed lot during germination and seedling emergence [15]. Previous research has suggested the presence of a positive linear relationship between seed vigor and seedling emergence in the field [16,17]. Tao et al found that there was an advantage in using high-vigor CMV seeds to achieve better seedling emergence, whereas low-vigor seeds caused limited seedling emergence [18].…”
Section: Introductionmentioning
confidence: 99%
“…Seed vigor is an important aspect of seed quality [14]; it is defined as the sum of the properties of the seed that determine the level of activity and the performance of a seed or seed lot during germination and seedling emergence [15]. Previous research has suggested the presence of a positive linear relationship between seed vigor and seedling emergence in the field [16,17]. Tao et al found that there was an advantage in using high-vigor CMV seeds to achieve better seedling emergence, whereas low-vigor seeds caused limited seedling emergence [18].…”
Section: Introductionmentioning
confidence: 99%
“…The radicle emergence (RE) test is simple method, which is indicative of the percentage of normal seedlings that is closely related to the germination speed index (GSI). The RE has been applied to a wide range of species such as Allium ampeloprasum (Ermis et al, 2015), Cicer arietinum (Akbarpour et al, 2019), or Lepidium sativum (Demir et al, 2019) and is an ISTA-validated as a vigour test for Zea mays (Matthews et al, 2011), Brassica napus (Powell et al, 2014), Raphanus sativus Mavi, 2016), andTriticum aestivum (Khajeh-Hosseini et al, 2019).…”
Section: Introductionmentioning
confidence: 99%